An assessment of a pulp and paper mill through energy and exergy analyses - Utlu, Zafer; Kincay, Olcay (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
In this study, a pulp and paper mill (PPM) in the SEKA Papermaking Plant in Izmit, Turkey, is analysed through energy and exergy balances. The plant utilises recycled waste paper for papermaking. This type of raw material input makes the process highly sophisticated. The pulping uses strictly mechanical processes, such as digestion, separation by screening and hydrocyclone, and refining. The milling, as an integrated process, provides the final operations necessary to prepare the conditions required for the end-product by stock-preparation, wiring, rolling, and drying by dewatering, pressing, and evaporation. The possibility of making the entire process more thermodynamically efficient is discussed by calculating the energy and exergy losses for all the mechanical and physical sub-processes. The study shows that the energy efficiencies for each of the mechanical and physical steps in the PPM vary between 34% and 97.4%, whereas the exergy efficiencies vary between 30.2% and 94.2%. In conclusion, based on the results from the energy and exergy flow analyses, the exergy output can be improved through more efforts directed primarily to further measurements toward more efficient energy utilisation in the PPM. Crown Copyright (c) 2013 Published by Elsevier Ltd. All rights reserved.
Keywords: Energy; Exergy; Pulp and paper mill; Recycled waste paper; UTILIZATION EFFICIENCY; EMPIRICAL-EVIDENCE; WASTE PAPER; INDUSTRY; COGENERATION; SYSTEM; MANAGEMENT; COUNTRIES; SOCIETY; SECTOR; Thermodynamics; Energy & Fuels